Antimicrobial and antibiofilm efficacy of a copper/calcium hydroxide-based endodontic paste against Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans - METO, Aida; COLOMBARI, Bruna; SALA, Arianna; PERICOLINI, Eva; METO, Agron; PEPPOLONI, Samuele; BLASI, Elisabetta (Dental Materials Journal, 2019)
Endodontic biofilm is a microbial community, enclosed in a polymeric matrix of polysaccharide origin where are found pathogens, like bacteria and opportunistic fungi responsible for various endodontic pathologies. As clinical importance is the fact, that biofilm is extremely resistant to common intracanal irrigants, antimicrobial drugs and host immune responses. The aim of this study was to evaluate the in vitro efficacy of a Cu/CaOH2-based endodontic paste, against bacteria and fungi, such as Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans. We found that such compound significantly reduced microbial replication time and cell growth. Moreover, biofilm formation and persistence were also affected; treated biofilms showed both a reduced number of cells and levels of released pyoverdine. This study provides the first evidence on effectiveness of this endodontic compound against microbial biofilms. Given its wide range of action, its use in prevention and treatment of the main oral biofilm-associated infections will be discussed.